1999
DOI: 10.1046/j.1440-1819.1999.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Precedents of perceived social support: Personality and early life experiences

Abstract: In order to examine the effects of personality and early life experiences on perceived social support, a total of 97 young Japanese women were investigated. Early life experiences at home and outside of home were also identified in the interview. The number of sources of perceived support was correlated with self-directness, while satisfaction with perceived support was correlated with novelty seeking and with low harm avoidance. No early life experiences -early loss of a parent, perceived parenting, childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…SD was also related to the number of supportive people in the subject's network (Kitamura, Kijima, Watanabe, Takezaki, & Tanaka, 1998). Terry, Rawle, & Callan (1995) showed that a better perception of social support by pregnant women could predict efficient coping behavior after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…SD was also related to the number of supportive people in the subject's network (Kitamura, Kijima, Watanabe, Takezaki, & Tanaka, 1998). Terry, Rawle, & Callan (1995) showed that a better perception of social support by pregnant women could predict efficient coping behavior after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…The SelfDirectedness construct includes cognitive functions such as self-esteem, internal locus of control, problem-solving, coping behaviors, and perceived support resources. Kitamura, Kijima, Watanabe, Takezaki, and Tanaka (1999) reported that higher Self-Directedness is related to the number of supportive people in the social network. The character dimensions are developed by psychotherapy (Cloninger et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the PBI have shown a general trend for patients with neurotic depression to score their parents low for care and high for overprotection (Parker, 1979(Parker, , 1981(Parker, , 1983aParker, Kiloh, & Hayward, 1987;Silove, Parker, Hadzi-Pavlovic, Manicavasagar, & Blaszczynski, 1991). Furthermore, the PBI has been widely used in psychosocial studies of current interpersonal relationships such as social supports (Kitamura, Kijima, Watanabe, Takezaki, & Tanaka, 1999;Parker, Barrett, & Hickie, 1992) or marital adjustment (Kitamura et al, 1995). The authors, however, know of few studies relating current health-related lifestyle to PBI scores.…”
mentioning
confidence: 99%